APPLICATION OF ANALYTICAL HIERARCHY PROCESS IN AGRICULTURE - Karmen Pažek; Č. Rozman (Poljoprivreda, 2005)
Hierarchical decision models are a general decision support methodology aimed at the classification or evaluation of options that occur in decision-making processes. Decision models are typically developed through the decomposition of complex decision problems into smaller and less complex subproblems. This paper presents an approach to the development and implementation of multicriteria decision model based on Analytical Hierarchy Process – AHP (Expert Choice, EC). Likewise, the AHP is used as a potential multicriteria decision making method for application in agriculture. In order to show the implementation of explained MCDA methods in real situation in agriculture, the application of AHP on a sample model farm is presented in the second part of the article.